PENERAPAN DAN EKSPLORASI TERAPI KECEMASAN PADA IBU DENGAN PREEKLAMPSIA DI MASA PANDEMI COVID-19 - Rinda Intan Sari; Anis Ardiyanti (NHM PRESS, 2022)
Background: Preeclampsia is one of the complications of pregnancy that causes maternal and fetal death. Pre-eclampsia increased anxiety due to complications and the Covid-19 pandemic. Continuous anxiety will have an impact on the health of the mother and fetus, including increase blood pressure, depression, premature uterine contractions, birth weight and premature. Objective: The purpose of this study was to reduce anxiety in pregnant women with preeclampsia. Methods: This study is a quantitative study by providing education, music therapy and aromatherapy with sample of 60 pregnant women with preeclampsia. Followed by qualitative research with in-depth interviews as an evaluation. Results : Giving Emak Kece therapy (education, music therapy and aromatherapy) has an effect on anxiety (p-value 0.000) so that it can decrease anxiety and for qualitative results obtained the theme (1) anxiety occurs depending on the increase and decrease in cases of covid19 (2) Education reduces anxiety (3) Music therapy and aromatherapy are not effective for those who do not like (4) Not all health workers provide intervention to reduce anxiety. Conclusion: Therapy to reduce anxiety is not only for pregnant women with preeclampsia but also for all pregnant women, to improve the quality of life in pandemic covid19.